2011
DOI: 10.1007/s12038-011-9042-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and molecular action of Trigonella foenum-graecum (fenugreek) and trace metals in experimental diabetic tissues

Abstract: Diabetes mellitus is a heterogeneous metabolic disorder characterized by hyperglycaemia resulting in defective insulin secretion, resistance to insulin action or both. The use of biguanides, sulphonylurea and other drugs are valuable in the treatment of diabetes mellitus; their use, however, is restricted by their limited action, pharmacokinetic properties, secondary failure rates and side effects. Trigonella foenum-graecum, commonly known as fenugreek, is a plant that has been extensively used as a source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 71 publications
3
67
0
Order By: Relevance
“…Hyperglycemia during diabetes has been shown to generate free radicals, increase damage to membranes and decrease antioxidant status (Kumar and Menon, 1993;Preet et al, 2005). Present results showed that three weeks treatment of the diabetic group with insulin, and TSP separately resulted in a marked reduction in hyperglycemia in the diabetic animals (Mohammad et al, 2006;Baquer et al, 2011;Kumar et al, 2011b, c). Na + K + ATPase and Ca 2+ ATPase play a role in the fine tuning of neuron functions which are decreased in diabetes due to oxidative stress and membrane damages (Pekiner et al, 2005;Kamboj et al, 2009).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Hyperglycemia during diabetes has been shown to generate free radicals, increase damage to membranes and decrease antioxidant status (Kumar and Menon, 1993;Preet et al, 2005). Present results showed that three weeks treatment of the diabetic group with insulin, and TSP separately resulted in a marked reduction in hyperglycemia in the diabetic animals (Mohammad et al, 2006;Baquer et al, 2011;Kumar et al, 2011b, c). Na + K + ATPase and Ca 2+ ATPase play a role in the fine tuning of neuron functions which are decreased in diabetes due to oxidative stress and membrane damages (Pekiner et al, 2005;Kamboj et al, 2009).…”
Section: Discussionmentioning
confidence: 55%
“…The plant material was identified in the literature of Ayurveda and by local experts of herbal gardens and further taxonomically validated. The most effective dose of 5% TSP in the diet has been determined in previous studies (Raju et al, 2001;Mohammad et al, 2006;Baquer et al, 2011;Kumar et al, 2011b, c).…”
Section: Experimental Designmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, there is a possibility that fenugreek seed extract may bring about some of its effects through increasing the expression of glucose transporter especially GLUT4 as previously reported [31].…”
Section: Discussionmentioning
confidence: 81%